Tumor Microenvironment‐Activated Hydrogel Platform with Programmed Release Property Evokes a Cascade‐Amplified Immune Response against Tumor Growth, Metastasis and Recurrence. Issue 50 (2nd November 2022) - Gong, Songlin; Liang, Xiuqi; Zhang, Miaomiao; Li, Lu; He, Tao; Yuan, Yuan; Li, Xinchao; Liu, Furong; Yang, Xi; Shen, Meiling; Wu, Qinjie; Gong, Changyang
Abstract: In situ tumor vaccines (ITV) have been recognized as a promising antitumor strategy since they contain the entire tumor‐specific antigens, avoiding tumor cells from evading immune surveillance due to antigen loss. However, the therapeutic benefits of ITV are limited by obstacles such as insufficient antigen loading, inadequate immune system activation, and immunosuppressive tumor microenvironments (TME). Herein, a tumor microenvironment‐activated hydrogel platform (TED‐Gel) with programmed drug release property is constructed for cascaded amplification of the anti‐tumor immune response elicited by ITV. Both doxorubicin (Dox) and cytosine‐phosphate‐guanosine oligodeoxynucleotides (CpG) are released first, in which Dox induces immunogenic tumor cell death causing additional tumor antigen release and leading the dying primary tumor cells into autologous tumor vaccine, and the released CpG promotes antigen presenting cell activation. Subsequently, the decomposed scaffold materials in conjunction with CpG, turn the anti‐inflammatory M2‐like macrophages into the M1 type, reversing the immunosuppressive TME. With decomposition of the TED‐Gel, large amounts of macromolecule anti‐PD‐L1 antibodies are liberated, reinvigorating the exhausted effector T cells. In vivo studies demonstrate that TED‐Gel significantly inhibits the primary, distant and rechallenged tumor growth. Overall, the simple and powerful TED‐Gel provides an alternative strategy for the future development of tumor vaccines with broad application. Abstract : A tumor microenvironment‐activated platform (TED‐Gel) is constructed with programmed drug release property to evoke a cascade‐amplified immune response. The TED‐Gel works by increasing the tumor antigen loads, boosting adaptive immunity and reversing the immunosuppressive TME at the same time. The injectable TED‐Gel with an organized drug release pattern provides for cascaded amplification of anti‐tumor immunity, resulting in robust and persistent systemic immune responses against tumor regression and the inhibition of tumor metastasis and recurrence.